Verification of X- and Y-spermatozoa separation by nested polymerase chain reaction (PCR), motility and membrane integrity in bovine - Abdul Malik,; Haron, Abd Wahid; Yusoff, Rosnina; Bukar, Muhammad Modu; Kasim, Azhar; Mohd Yusoff, Md Sabri (Academic Journals, 2011)
The aim of the present study was to verify the presence of X- and Y-chromosome spermatozoa after separation with swimming speed using oestrus cows vagina mucus, Percoll discontinuous gradient (45 to 90%) and swim-up using TALP medium. The nested polymerase chain reaction (PCR) was used to determine X- and Y-chromosome bearing spermatozoa after separation. The primers for PCR were designed using amelogenin cDNA sequence with 329 and 266 bp for X- and Y-bearing chromosome spermatozoa, respectively. The motility was analyzed using computer assisted sperm analyser, whereas the membrane integrity was analyzed using hypo-osmotic swelling test (HOST). Results were confirm by the absence of single band, either for X- or Y-chromosome. Inversely, the double band indicating that the spermatozoa cannot be separated was observed. The percentage of X-chromosome bearing spermatozoa in the swimming speed using oestrus cows vagina mucus media, Percoll discontinuous gradient and swim up methods were 58.33, 44.33 and 50%, respectively. Statistically, both percentages were significantly different (P<0.001) as compared to the theoretical ratio (50:50). Spermatozoa motility, membrane integrity and concentration before and after separation were also significantly different (P<0.05). This study shows that although swimming speed using oestrus cow’s vagina mucus media may be used to separate X- and Y-chromosome bearing spermatozoa in bulls, the results however, require further investigation.